2001
DOI: 10.1007/s00468-001-0126-6
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, wood structure and cell wall composition of rolC transgenic and non-transformed aspen trees

Abstract: Morphology, wood structure and cell wall composition of 35S-rolC transgenic hybrid aspen (P. tremula×tremuloides) were compared with non-transformed control trees. The transgenics are characterised by stunted growth, altered physiological parameters and light green leaves of reduced size. Histometric measurements revealed thinner fibre walls as compared to the controls. UV microspectrophotometry of individual wall layers did not reveal distinctive differences in the lignification of xylem cells, but in the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 42 publications
1
11
1
Order By: Relevance
“…Work along this line includes studies of the deposition of cell wall components during the differentiation of xylem cells in normal and 35S-rolC transgenic hybrid aspen Populus tremula 9 P. tremuloides, (Dünisch et al 2006;Grünwald et al 2001Grünwald et al , 2002a, which has a dwarfed phenotype. In the wild-type, polysaccharides were deposited before the lignin during cell wall formation, while these two events proceeded more in parallel in the transgenic plants.…”
Section: Uv-vis Spectra Of Lignin and Other Ring Structuresmentioning
confidence: 99%
“…Work along this line includes studies of the deposition of cell wall components during the differentiation of xylem cells in normal and 35S-rolC transgenic hybrid aspen Populus tremula 9 P. tremuloides, (Dünisch et al 2006;Grünwald et al 2001Grünwald et al , 2002a, which has a dwarfed phenotype. In the wild-type, polysaccharides were deposited before the lignin during cell wall formation, while these two events proceeded more in parallel in the transgenic plants.…”
Section: Uv-vis Spectra Of Lignin and Other Ring Structuresmentioning
confidence: 99%
“…Differences in the composition of lignin in the various layers of the xylem cell wall have an effect on fiber properties and hence the quality of paper pulp. Variations in the topochemistry of condensed and non-condensed lignin substructures have already been revealed in hardwood lignin (Ruel et al 1999;Gru¨nwald et al 2001) and in Gramineae (Joseleau and Ruel 1997), by the use of different immunological probes raised against synthetic lignin polymers (Ruel et al 1994;Joseleau and Ruel 1997). In this study, a specific antibody against the dibenzodioxocin substructure was generated and used as a probe, allowing a detailed analysis of the lignin composition in softwood xylem cell walls.…”
Section: Introductionmentioning
confidence: 96%
“…Microscopic analyses did not reveal significant differences in the structure of xylem cell walls between 35S-rolC transgenic and wild type trees. Although histometric measurements have shown slightly reduced vessel lumen areas and fibre lengths as well as thinner fibre cell walls in the 35S-rolC transgenic than in the wild type trees, no evidence was found for an alteration of cell wall chemistry in the differentiated wood [15,16]. Therefore, it can be concluded that in the wild type trees lignification was not completed within 40 cell rows from the cambium, even in middle lamella regions, which are known to lignify more rapidly and intensely than the secondary walls [36].…”
Section: Discussionmentioning
confidence: 90%
“…In the 35S-rolC transgenic aspen trees used in the present study, physiological and morphological traits were distinctly modified [12,13]. In particular, in the xylem tissue no typical latewood was formed and an unusual high amount of gelatinous fibres was conspicuous; at the cellular level the general morphology of fibres, vessels and parenchyma cells appeared unchanged, although the formation and differentiation of these cells was delayed [15,16].…”
Section: Introductionmentioning
confidence: 95%